The Construction of meaning in film a case study of "The Unique oneness of Christian Savage" - Ussi, Jennifer; O'Casey, Anne; Miller, Cathy; John Davis (Coquitlam, B. C. : Classroom Video, 1999)
Examines the composition of the film'The Unique Oneness of Christian Savage' by Jennifer Ussi
Writer and producer, Anne O'Casey ; editor, Phil Sheppard ; executive producers, Cathy Miller, John Davis
Keywords: Motion pictures -- Production and direction; Cinematography